Influence of fintech on management transformation - Sghari, Amira, 1982-; Mezghani, Karim, 1979- (Advances in finance, accounting, and economics (AFAE) book series., 2021)
"This book consolidates knowledge in management in a context of digital transformation offering explanations of how the management transformation in financial institutions and companies is closely related to the emergence of fintech"--